COVID-19 cardiac arrest management: A review for emergency clinicians (2020)
Introduction: A great deal of literature has recently discussed the evaluation and management of the coronavirus disease of 2019 (COVID-19) patient in the emergency department (ED) setting, but there remains a dearth of literature providing guidance on cardiac arrest management in this population. Objective: This narrative review outlines the underlying pathophysiology of patients with COVID-19 and discusses approaches to cardiac arrest management in the ED based on the current literature as well as extrapolations from experience with other pathogens. Discussion: Patients with COVID-19 may experience cardiovascular manifestations that place them at risk for acute myocardial injury, arrhythmias, and cardiac arrest. The mortality for these critically ill patients is high and increases with age and comorbidities. While providing resuscitative interventions to and performing procedures on these patients, healthcare providers must adhere to strict infection control measures and prioritize their own safety through the appropriate use of personal protective equipment. A novel approach must be implemented in combination with national guidelines. The changes in these guidelines emphasize early placement of an advanced airway to limit nosocomial viral transmission and encourage healthcare providers to determine the effectiveness of their efforts prior to placing staff at risk for exposure. Conclusions: While treatment priorities and goals are identical to pre-pandemic approaches, the management of COVID-19 patients in cardiac arrest has distinct differences from cardiac arrest patients without COVID-19. We provide a review of the current literature on the changes in cardiac arrest management as well as details outlining team composition.